Alternatywny scenariusz biografii muzyka rockowego – o życiu i twórczości Jasona Beckera - Kosek, Jakub (Kultura-Społeczeństwo-Edukacja, 2016)
The article focuses on the analysis of the biography of an American rock guitarist, namely Jason Becker. The main object of this study was the documentary „Jason Becker. Not Dead Yet” (2012) and some selected press news and information available on social media. The original biography of the musician, who within a few years has become famous in the world of rock music and since the age of 19 has had to confront the incurable disease – amyotrophic lateral sclerosis – is an interesting example of the alternative model of a biography in popular culture. It is also an educational story that teaches fundamental values, such as altruism, love, respect and friendship.